EFEKTIVITAS LITERASI DIGITAL DALAM MENINGKATKAN KOMPETENSI BAHASA INGGRIS MAHASISWA BERBASIS BLENDED LEARNING : EFEKTIVITAS LITERASI DIGITAL DALAM MENINGKATKAN KOMPETENSI BAHASA INGGRIS MAHASISWA BERBASIS BLENDED LEARNING - Nur Eva Yanti; Maenuddin Bustanil Syah; Nuraini Yusuf (Institut Teknologi dan Bisnis Bina Adinata, 2024)
This study aims to measure the effectiveness of digital literacy in improving the English language competence of students based on blended learning at Universitas Ichsan Sidenreng Rappang. Digital literacy plays a crucial role in helping students access, process, and filter information, especially in the context of learning English. The research method used is a quantitative experiment with a one-group pretest-posttest design, involving 30 students who participated in an English language course based on blended learning. The primary instrument used in this study is an English proficiency test that measures four skills: reading, writing, listening, and speaking. The results show a significant improvement in students' English competence after participating in the digital literacy-based blended learning program. Based on the gain score calculation, the average score of students increased from 35.67 in the pretest to 84.23 in the posttest, with a gain score of 0.75. These findings indicate that digital literacy can effectively improve students' English skills, particularly in basic literacy skills such as reading and writing, which supports the success of blended learning. Keywords: Digital Literacy, English Language Competence, Blended Learning, Technology-Based Learning, Gain Score